The Development of Fantasy Teaching Materials by Using VAK (Visual Auditory Kinesthetic) on 7th Grade Students in SMP Negeri 1 Medan - Nurul Jamiah Rangkuti; Khairil Ansarif; Wisman Hadi (BIRCU, 2020)
This study aims to produce teaching materials by using VAK (Visual Auditory Kinestethic) on fantasy story material for 7th grade students of SMP Negeri 1 Medan. The research method used is Research and Development which refers to Borg and Gall model. The stages of development are the initial study phase, initial product development, and product trials. The results showed that the results of material validation included content eligibility with an average of 82% with a very good category, Eligibility for Presentation with an average of 87.5% with a very good category, and an assessment of language aspects with an average of 82.2% with a category very good. For the assessment of graphics by design experts obtained an average of 87% with the category